1985
DOI: 10.1002/1097-0142(19850815)56:4<905::aid-cncr2820560435>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

The malignant pleural effusion. A review of cytopathologic diagnoses of 584 specimens from 472 consecutive patients

Abstract: This study reports the cytopathologic diagnoses rendered on all malignant pleural effusions received and processed over a period of 14 years. Specimens of fluid from various body sites (25,464) were examined. Of these, 5888 (23%) were specimens of pleural effusions. Five hundred eighty-four specimens (9.9% of total pleural fluid specimens) taken from 472 patients were diagnosed as containing cancer cells. Of the malignant pleural effusions, 75.7% were classified as carcinomatous in type. Adenocarcinomas compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
204
6
11

Year Published

1987
1987
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(233 citation statements)
references
References 12 publications
12
204
6
11
Order By: Relevance
“…In the present study, all of the effusions were exudates, with a slight increase in the levels of protein and lactate dehydrogenase. Although increased triglyceride levels in pleural fluid have been reported in cases of lymphoma, (13,14,17) only 4 (≈14%) of the lymphoma patients investigated in the present study showed triglyceride levels higher than 110 mg/dL, which explains the low mean values obtained in that group, as well as the absence of statistical significance when those values were compared with those obtained in the tuberculosis group. Although high levels of cholesterol in pleural fluid are associated with pseudochylous effusions, a condition that is generally associated with chronic fluid collections, (21) cholesterol in pleural fluid can be used in order to classify pleural exudates.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…In the present study, all of the effusions were exudates, with a slight increase in the levels of protein and lactate dehydrogenase. Although increased triglyceride levels in pleural fluid have been reported in cases of lymphoma, (13,14,17) only 4 (≈14%) of the lymphoma patients investigated in the present study showed triglyceride levels higher than 110 mg/dL, which explains the low mean values obtained in that group, as well as the absence of statistical significance when those values were compared with those obtained in the tuberculosis group. Although high levels of cholesterol in pleural fluid are associated with pseudochylous effusions, a condition that is generally associated with chronic fluid collections, (21) cholesterol in pleural fluid can be used in order to classify pleural exudates.…”
Section: Discussioncontrasting
confidence: 78%
“…(14,(16)(17)(18) In addition, ADA levels are commonly increased in the pleural fluid of patients with lymphoma, regardless of the cell subtype (T or B cells). (13) From a clinical standpoint, both tuberculosis and lymphoma predominate in males in the second decade of life, although tuberculosis can also affect younger patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While NSCLC is the most common cause of malignant disease of the pleura, the pleural model used in this study is also relevant to other cancer types, including mesothelioma, breast, ovarian, and lymphoid cancers (48)(49)(50). Pleural spread of NSCLC is thought to result from either exfoliation and/or lymphatic spread.…”
Section: Discussionmentioning
confidence: 99%
“…20,28,29 Lymphocytes predominant in tubercular pleural effusion. Cytology for malignant cells was positive in 33-87%; Light demonstrated predominantly polymorphs in bacterial pneumonia.…”
Section: Pleural Fluid Cytologymentioning
confidence: 99%